Capabilities of Forensic Molecular Genetic Analysis in Establishing the Taxonomic Aﬃliation of Objects of Plant Origin - G. G. Omel'yanyuk; O. B. Gradusova; I. V. Storozhenko; A. A. Rybakova (Теория и практика судебной экспертизы, 2021)
The control over the circulation of plants containing narcotic drugs or psychotropic substances (or their precursors) is one of the most critical aspects of the ﬁght against drug crime. The forensic botanical examination uses classical morphological and anatomical analysis methods, which are not always informative enough when identifying species membership of shredded and degraded plant objects; similarly, they do not allow to establish their individual-speciﬁc identity. The molecular genetic methods of plant analysis and the comparative databases could serve as valuable tools for law enforcement purposes. In particular, in the production of forensic molecular genetic analysis of narcotic plants presented in powder, it is crucial to determine the taxonomic aﬃliation of the objects since this information aﬀects the qualiﬁcation of the crime. As a case the author presents the materials of an additional forensic examination conducted in the Russian Federal Centre of Forensic Science of the Ministry of Justice of the Russian Federation, the results of which had a signiﬁcant impact on the qualiﬁcation of the committed oﬀense.